The importance of fields of expertise and educational advice in Saudi Arabia from the point of view of educational leaders and supervisors - AlMohammadi, Mansoor Gahzi (Technium Social Sciences Journal, 2022)
The study aimed to determine the areas in which houses of expertise and educational consultancy in education departments in the Kingdom of Saudi Arabia may offer improvement from the point of view of educational leaders and supervisors. The study sample consisted of 217 educational supervisors, 222 school leaders, and 439 other individuals. The result shows that, the integration of the application of information technology”, Digital Transformation and Technology Support in the field of study may help educational advice. In light of the results, the researcher advocated a set of recommendations.